IMPLEMENTASI PERDA KOTA PEKANBARU NOMOR 14 TAHUN 2000 TENTANG IZIN BANGUNAN DALAM DAERAH KOTA PEKANBARU (Studi Kasus Kecamatan Tampan) - Rahmawan, Rio Ryan; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Much difference between who has a license with an unlicensed that from 2010to 2012 data do not take care of as much as 1277 building permit and take care ofIMB data from 2010 to 2012 amounted to 895. Thus, the data permit an unlicensedmore than to have a permit. Phenomena that are found in this study that most peopleare not clearly know the procedures on how to apply for a building permit, low publicawareness about the importance of BMI in the arrangement of buildings in setting upthe building, supervision of spatial planning and building department itself until nowthis is still lacking.The concept of the theory that the researchers use a policy theory, Theory ofPolicy Implementation. This study uses qualitative research methods to studydescriptive data. In collecting the data, the researcher used interview, observation anddocumentation. By using key informants as a source of information.The results showed that on the Implementation of Pekanbaru City RegulationNo. 14 of 2000 on Building Permits in Pekanbaru City Region (Case Study District ofHandsome) based on indicators, it can be concluded that surveillance conducted bythe Department of Spatial Planning and Building Pekanbaru has not gone wellbecause they scarcity of authorized personnel to evaluate and follow up errors andshortcomings of existing officers, lack of public awareness of the regulations thathave been made by the government so that government regulation is lessterimplemntasi well.Keywords: Implementation, Policy, Building permit